Przywódca jako strateg - Szpineter, Jerzy; Dulewicz, Leon (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article is devoted to strategic management which is presented as one of the most important tasks carried out by management of any organization. Theoretical discussion (based on P.F. Drucker's and M.Porter's ideas) is supported by examples of solutions applied successfully in ZWSS Belos company in Bielsko-Biała. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 150-157